Development of Glucose Meter Using Boric Acid-Modified Carbon Dots as Fluorescent Probe - Maddu, Akhiruddin; Ahmad, Sejahtera; Sumaryada, Tony (Photonics Letters of Poland, 2021)
A glucose meter has been developed utilizing boric acid-modified carbon dots as a fluorescence probe. Boric acid-modified carbon dots produces varying fluorescence emission with varying glucose concentration in water. Boric acid-modified carbon dots mixed with glucose addition was excited by a violet laser (405 nm), then the emission intensity was detected by a photodetector to be converted to an electrical signal that as an input signal for a microcontroller for glucose concentration measurement. The output voltage of the glucose meter is corresponding to the fluorescence emission measured by using a spectrofluorometer with glucose concentration in the boric acid-modified carbon dots. Full Text: PDF References H. Teymourian, A. Barfidokht, J. Wang, "Electrochemical glucose sensors in diabetes management: an updated review (2010–2020)", Chem. Soc. Rev. 49, 7671 (2020). CrossRef D.C. Klonoff, "Overview of Fluorescence Glucose Sensing: A Technology with a Bright Future", J Diabetes Sci. Technol. 6(6), 1242 (2012). CrossRef J.C. Pickup, F. Hussain, N.D. Evans, O.J. Rolinski, David J.S. Birch, "Fluorescence-based glucose sensors", Biosens. Bioelectron. 20, 2555 (2005). CrossRef H. Fang, G. Kaur, B. Wang, "Progress in Boronic Acid-Based Fluorescent Glucose Sensors", J. Fluoresc. 14(5), 481 (2004). CrossRef T. Kawanishi, M.A. Romey, P.C. Zhu, M.Z. Holody, S. Shinkai, "A Study of Boronic Acid Based Fluorescent Glucose Sensors", J. Fluoresc. 14(5), 499 (2004). CrossRef A.S. Krishna, P.A. Nair, C. Radhakumary, K. Sreenivasan, "Carbon dot based non enzymatic approach for the detection and estimation of glucose in blood serum", Mater. Res. Express 3(1), 055001 (2016). CrossRef G.P.C. Mello, E.F.C. Simões, D.M.A. Crista, J.M.M. Leitão, L. Pinto da Silva, J.C.G. Esteves da Silva, "Glucose Sensing by Fluorescent Nanomaterials", Crit. Rev. Anal. Chem. 49(6), 542 (2019). CrossRef X. Shan, L. Chai, J. Ma, Z. Qian, J. Chen, H. Feng, "B-doped carbon quantum dots as a sensitive fluorescence probe for hydrogen peroxide and glucose detection", Analyst 139, 2322 (2014). CrossRef J. Dong, S. Li, H. Wang, Q. Meng, L. Fan, H. Xie, C. Cao, W. Zhang, "Simple Boric Acid-Based Fluorescent Focusing for Sensing of Glucose and Glycoprotein via Multipath Moving Supramolecular Boundary Electrophoresis Chip", Anal. Chem. 85(12), 5884 (2013). CrossRef Y. Cui, F. Chen, X-B. Yin, "A ratiometric fluorescence platform based on boric-acid-functional Eu-MOF for sensitive detection of H2O2 and glucose", Biosens. Bioelectron. 135, 208 (2019). CrossRef